PEER TUTOR LEARNING ASSISTED BY MIND MAPPING TO IMPROVE BIOLOGY LEARNING OUTCOMES - Nur, Syamsiara; Irfan, M.; Alfiani, Nur (Universitas PGRI Sumatera Barat, 2023)
This research aims to determine the influence of peer tutoring with the aid of mind mapping in improving biology learning outcomes. The study was conducted using a quasi-experimental pretest-posttest control group design. The sample for this research was 11th-grade students at SMA Negeri 1 Sendana enrolled in the Odd Semester of the Academic Year 2022/2023, with the subject matter being the structure and function of plant tissues. The research sample consisted of two classes, an experimental class, and a control class, selected using purposive sampling. The experimental class utilized peer tutoring with mind mapping, while the control class employed conventional teaching methods involving lectures and question-and-answer sessions. The research instrument used was a 30-item multiple-choice test. Data analysis was performed using one-way ANCOVA. The calculation results indicated that the significance value (sig) <0.05, leading to the conclusion that H0 was rejected, and H1 was accepted. This means that peer tutoring with the aid of mind mapping resulted in higher learning outcomes compared to students who received conventional teaching methods.